Чернігівська фортеця 1677 р.: московська залога - Ситий, І. (Сiверянський літопис, 2020)
Метою дослідження є огляд особливостей функціонування московських залог на території Гетьманщини у другій половині XVII ст., а також введення до наукового обігу інформації щодо чернігівської залоги у 1677 р. з архівних джерел фондів Російського державного архіву давніх актів. Методологічно робота побудована на засадах соціокультурного підходу. Наукова новизна полягає у тому, що вперше здійснений аналіз документів, які було присвячено різним аспектам існування московської залоги у Чернігові станом на 1677 р. Отримані результати дослідження виявилися доволі репрезентативними, щоб уявити умови діяльності так само й інших залог в межах Гетьманщини. Висновки. У статті висвітлена поява московських залог в козацькій Україні. На прикладі відповідної залоги 1677 р. у Чернігові проаналізовані роль і функції воєвод, забезпечення провіантом і фуражем, порядок передачі фортеці від одного воєводи до іншого, кількісний і якісний склад офіцерського та рядового складу, оплата служби військових, юридичні підвалини функціонування гарнізонів, комунікація із центральними органами влади, відносини з міщанським та козацькими урядами, облога в місті на Десні московського підрозділу гетьманом Іваном Брюховецьким у 1668 р., формування російсько-української мікроспільноти через шлюб вояків з українками, а також про забезпечення контролю українських земель під владою Великого князівства Московського. Українське населення залог перебувало під юрисдикцією козацьких та міщанських урядів, проте, як свідчать факти, навіть представники вищих прошарків Гетьманщини були вразливі від свавілля московських ратників. Українки, які брали шлюб з москалями, та діти від такого шлюбу автоматично переходили до московської юрисдикції. Головним завданням залог був контроль над підлеглими українськими територіями, і ми мусимо визнати, що це завдання було виконане. The purpose of the study was to review the peculiarities of the functioning of the Moscow pledges on the territory of Hetmanate in the second half of the 17th century, especially in the Chernihiv fortress in 1677. Methodologically the work is based on the socio-cultural approach. The scientific novelty is the first analysis of documents that dealt with various aspects of the existence of the Moscow pledge in Chernihiv in 1677. The results of the study were quite representative to represent the conditions of activity of other pledges within Hetmanate.
Conclusions. The article highlights the emergence of Moscow pledges in Cossack Ukraine. The example of the corresponding pledge in 1677 in Chernihiv analyzed the role and functions of the voivode, provision of food and feed, the order of transfer of the fortress from one voivode to another, the quantitative and qualitative composition of officer and rank, payment military, legal bases for the functioning of the pledge,
communication with the central authorities, relations with bourgeois and Cossack governments, the siege of Moscow garrison Chernihiv Hetman Ivan Bryukhovetsky in 1668, forms tion of Russian-Ukrainian mikrospilnoty through marriage with Ukrainian soldiers, part pledge to provide control of Ukrainian lands ruled by the Grand Duchy of Moscow.
The emergence of Moscow pledges in the Hetmanate was conditioned by interstate treaties between the Ukrainian and Moscow governments. In their activities, they were guided by Moscow law and current charters and decrees of the tsarist government and the Order of Little Russia, to which they directly obeyed. In addition, they operated under the central pledge of Moscow in Ukraine – the Kiev, represented by the respective governor. Communication and correspondence pledge happened so to speak at three addresses – Moscow (tsar and government), Kyiv (voivode). The third copy of the document identified in the order remained in the deposit archive. Contact with the center was provided by Baturyn Post and messengers – by land by horse transport (carts, sledges) or by river, by boat. Pledges consisted of two components – Russian shooters and soldiers. The latter were commanded by foreign mercenary officers. In addition to combat training, the personnel was responsible for the engineering work to repair and strengthen the fortifications. On it lay various economic works – construction and repair of auxiliary structures (“crates, barns, barns”, smithies, etc.), harvesting of grain, fodder, baking of bread, etc. By marital status, it was divided into singles and marital. Many marriages had a mixed character – a Russian man, a Ukrainian woman. However, some of the warriors had a second family in the Moscow region. The pay of the warriors consisted of two parts – monetary remuneration and natural compensation (bread and salt) according to the established norms. The lion’s part was first shipped from Moscow, ancillary at the expense of specially built taverns. The calculations were made according to the Moscow monetary system (ruble, half-dollar, altin, money), taking into account the Ukrainian (Czech). As a rule, the number of collateral did not correspond to the designated state. She was affected by combat losses, illnesses, escapes, the absence of a reserve component in Muscovy, and delayed pay. After a few years of service, the warrior could count on a rotation. The command staff was completed with the sent officers and by nomination of the rank and file officers who were distinguished in the service.
The Ukrainian population was under the jurisdiction of the Cossack and bourgeois governments, but according to the facts, even representatives of the higher strata of the Hetmanate region were vulnerable to the arbitrariness of the Moscow warriors. It should be added that Ukrainians who were married to Muscovites and children from such marriage were automatically transferred to Moscow jurisdiction.
The main function of the pledge was to control the subordinate Ukrainian territories, and they must cope with it.